EFFECT OF CUSTOMIZATION AND SOCIAL BONDING ON CUSTOMER LOYALTY MEDIATED BY TRUST VARIABLES - Patwayati; Marsini (Russian Journal of Agricultural and Socio-Economic Sciences, 2020)
This research was conducted with the aim of knowing and analyzing the effect of customization and social ties on customer loyalty mediated by the variable of trust. The population in this study is the customer at the South Sulawesi Branch Bank Punggaluku. The total customers of Bank Sultra Punggaluku Branch in 2017 are around 2000 customers. The sample method in this study was determined using the Accidential sampling method. So that the sample taken can be said to be representative, then in this study using the Slovin formula, the sample in this study was determined as many as 116 customers, with sample criteria, namely: 1. Customers who are directly related to multipurpose loans, namely civil servants in southern Konawe, 2. Customers who have multipurpose credit facilities, 3. Customers who have experienced multipurpose loans for about 1 year. The analytical tool used is SEM. The research results obtained based on the results of the analysis are that: 1. Customization ties have a positive and significant effect on the trust of customers in multipurpose banking at South Sulawesi Branch of Punggaluku; 2. Social ties have a positive and significant effect on the trust of multipurpose credit customers at the South Sulawesi Bank Punggaluku Branch; 3. The customization bond has a positive and significant effect on the loyalty of multipurpose loan customers at the South Sultra Bank, Punggaluku Branch; 4. Social ties have a positive and significant effect on the loyalty of multipurpose credit customers at the South Sulawesi Bank Branch, Punggaluku; 5. Trust has a positive and significant effect on the loyalty of multipurpose loan customers at the South Sulawesi Regional Bank Punggaluku Branch; 6. Customization ties have a positive and significant effect on customer loyalty through the trust of customers of multipurpose credit at Bank Sultra Punggaluku Branch; 7. Social ties have a positive and significant effect on customer loyalty through the trust of multipurpose credit customers at the South Sulawesi Bank Punggaluku Branch.